Combined electro-catazone/electro-peroxone process for rapid and effective Rhodamine B degradation - Li, Xinyang; Sun, Shaobin; Zhang, Xu; Liu, Guicheng; Zheng, Clark Renjun; Zheng, Jianzhong; Zhang, Dayi; Yao, Hong (ELSEVIER SCIENCE BV, 2017)
An integral electro-catazone and electro-peroxone (E-cataperoxone) process was developed for quick and effective oxidation of Rhodamine B (RhB) as the model refractory organic pollutant in this study. A mesoflower-structured TiO2-coated porous Titanium gas diffuser (MFT-PTGD) acted as both the anode and the O-3 gas diffuser, while carbon polytetrafluoroethylene was used as the cathode. During O-3/O-2 mixture flowing through the MFT-PTGD, O-3 was electrochemically catalyzed simultaneously by the TiO2 mesoflower at the anode (via an electro-catazone reaction) and the in situ generated H2O2 at the cathode (via an electro-peroxone reaction) to achieve a high yield of (OH)-O-center dot. The E-cataperoxone process shows an integral effect and significantly enhances the RhB degradation rate and efficacy. Additionally, owing to the unique three-dimensional porous structure and flow-through configuration of the MFT-PTGD anode, the O-3 flow-through mode is superior to O-3 flow-by mode for the E-cataperoxone oxidation of RhB. These results suggest that the E-cataperoxone process is an effective and promising means of degrading refractory organic pollutants in wastewater. (C) 2017 Elsevier B.V. All rights reserved.